Pentraxin-3: A Novel Marker for Indicating Liver Fibrosis in Chronic Hepatitis B Patients? - Balin, Safak Ozer; Cabalak, Mehmet; Tartar, Ayse Sagmak; Kazanci, Ulku; Telo, Selda; Demirdag, Kutbeddin; Akbulut, Ayhan (Aves, 2021)
Background: Pentraxin-3 (PTX-3) is an important marker that plays a role in suppressing inflammation and tissue repair. The aim of this study is to investigate the diagnostic and prognostic characteristics of PTX-3 in chronic hepatitis B (CHB) patients and the relationship between PTX-3 levels and fibrosis. Methods: A total of 52 CHB patients and 40 healthy subjects were included in the study. All of the CHB patients underwent liver biopsy and were then scored using an Ishak histologic scoring system. Blood samples were collected to evaluate the PTX-3 levels. Results: Of the subjects who participated in the study, 53% were female. The PTX-3 levels were determined as 5.63 ng/mL in the control group, and as 0.88 ng/mL in the CHB patient group. PTX-3 levels were found to be 1.19 ng/mL in stage 1, 0.89 ng/mL in stage 2, 0.68 ng/mL in stage 3, and 0.55 ng/mL in stage 4. Of the CHB patients, 44.2% had significant fibrosis, while 55.7% were identified as not having significant fibrosis. The PTX-3 values were 0.64 and 1.0 ng/mL in patients with and without significant fibrosis, respectively. The cut-off value for PTX-3 in predicting the absence of significant fibrosis was estimated as 0.9 ng/mL. Conclusion: The CHB patients were found to have lower serum PTX-3 levels compared to the control group, and these levels decreased even further as the stage of fibrosis progressed. In addition, the significant decrease in PTX-3 levels in patients with stage 1 fibrosis compared to the control group shows that PTX-3 can be used as a non-invasive marker for the early detection of fibrosis (P <.001).
Keywords: Chronic hepatitis B; fibrosis; Pentraxin-3